2012
DOI: 10.3109/02652048.2012.655330
|View full text |Cite
|
Sign up to set email alerts
|

Development of photostable gastro retentive formulation for nifedipine using low-density polypropylene microporous particles

Abstract: The aim of this study was to develop photostable gastro retentive formulation for nifedipine loading into low-density polypropylene microporous particles (Accurel MP 1000®) by a solvent evaporation technique using the 3² factorial design. Yield, drug loading, surface topography, thermal properties, crystal characteristics, photostability and in vitro drug release were studied. Optimized microparticles formulated into a capsule were evaluated for the dissolution study and compared with marketed formulation. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The EBMG exhibited a burst effect within 2 h (98.3 ± 7.0 μg/cm 2 ) due to the presence of nonencapsulated drug closer to the surface or on the surface of the microsponges, which does not produce irritation to the skin. After that, a linear relationship existed for up to 12 h due to the porous nature of the microsponges providing the channel for drug release [22]. The slopes (flux) of the linear portion of the permeation profiles were calculated.…”
Section: Ex Vivo Diffusion Studymentioning
confidence: 99%
“…The EBMG exhibited a burst effect within 2 h (98.3 ± 7.0 μg/cm 2 ) due to the presence of nonencapsulated drug closer to the surface or on the surface of the microsponges, which does not produce irritation to the skin. After that, a linear relationship existed for up to 12 h due to the porous nature of the microsponges providing the channel for drug release [22]. The slopes (flux) of the linear portion of the permeation profiles were calculated.…”
Section: Ex Vivo Diffusion Studymentioning
confidence: 99%
“…Nifedipine is extremely unstable to light and undergoes photocatalytic disproportionation of the molecule when exposed to light (i.e., degradation), producing nitro-pyridine derivatives and benzopyridine nitrite derivatives that are harmful to humans, which leads to harsh storage conditions for nifedipine. 67 As shown in Fig. 7a, nifedipine transforms from a brighter yellow-green color to a darker brownish-red color under sunlight exposure.…”
Section: Performance Characterization Of Spherical Productsmentioning
confidence: 95%
“…To our knowledge, only a few examples in the literature deal with describing the effect of the drug state on its release kinetic from nanocarriers. Indeed, a significant change in the crystallinity of the polymer and the native drug may affect the drug release rate and subsequently its release kinetics [27] . Powdered X-ray Diffraction (PXRD) analysis revealed that DOC became amorphous and was likely to be dissolved within the NCs' oily core and probably in the PLA shell.…”
Section: Introductionmentioning
confidence: 99%